Model for a maritime logistic supply chain for captured CO2 in Sweden - Bruguera Matute, Gemma; Castro Molinero, Antonio Juan (My University, 2023)
This master’s thesis report presents the results of the research carried out for the design of an optimal marine logistic chain for CO2 transportation in Sweden. The effectiveness of CO2 transport systems is related to the output of the Carbon Capture (CC) facilities, inland feeder traffic, intermediate storage hubs and type and cost of liquefaction plants among others. The solution is reached by means of a mathematical model built up so that the optimal fleet logistic can be found for a specific defined scenario, i.e., number of vessels that compounds the fleet, sizes of the ships in terms of its cargo capacity and sailing speed. Additionally, a cost breakdown of the mentioned logistic chain is presented in order to identify the origin and percentage of each variable contributing to the total cost. Results from this study indicate that the largest contributor to the CCS chain considered is the liquefaction process, followed by the fleet cost. In addition, medium pressure transport is always the most expensive option in comparison with low pressure transport and using the largest ship capacity is almost always more economical. This is because the increase in the cost of buffer storage is not as great as the increase in the cost of the fleet due to the increase in the number of ships per fleet.
Keywords: CCS; CCU; maritime logistics; CO2; maritime decarbonization; Sweden; supply chain